Enhancement of the performance of kesterite thin-film solar cells using dual absorber and ZnMgO buffer layers - Mohammadnejad, Shahram; Mollaaghaei Bahnamiri, Zeinab; Enayati Maklavani, Shahin (Superlattices and microstructures, 2020)
A new structure of kesterite thin-film solar cells is simulated using SCAPS software. In addition, the structures of CZTS/ZnMgO, CZTSSe/CZTS/CdS and CZTSSe/CZTS/ZnMgO are suggested and scrutinized. In CZTS/ZnMgO structure, the efficiency, open-circuit voltage and short circuit current at the absorber layer thickness of 3 μm have been improved 35%, 15%, and 15% respectively. Furthermore, the efficiency of the proposed solar cell has been enhanced 60% by adding the CZTSSe absorber layer on the back of the CZTS layer. The optimum buffer layer thickness in the structures of CZTSSe/CZTS/CdS and CZTSSe/CZTS/ZnMgO are 150 nm and 125 nm, respectively. The simulation results show that the basic photovoltaic parameters (VOC, JSC, FF and η) have been decreased by variation of temperature from 300 K to 400 K. The optimal bandgap of the CZTSSe and ZnMgO in the structure of CZTSSe/CZTS/ZnMgO are obtained 0.9eV and 3.48eV, respectively in the ZnMgO optimal thickness of 50 nm. The highest efficiency of the kesterite solar cell with Zn0.81Mg0.19O buffer layer is 17.05%. •CZTS based thin film solar cells (Mo/CZTS/Buffer/i-ZnO/ZnO:Al/Al) with CdS and proposed ZnMgO buffer layers have been compared and simulated by SCAPS-1D.•The highest performance of device have been obtained using CZTSSe absorber layer in the back of CZTS layer (Mo/CZTSe/CZTS/Buffer/i-ZnO/ZnO:Al/Al) and optimization of the proposed structure.•Results show that the optimum buffer layer thickness in the structures of CZTSSe/CZTS/CdS and CZTSSe/CZTS/ZnMgO are 150 nm and 125 nm, respectively.•In dual absorber-based structure with CdS and Zn0.81Mg0.19O buffer layers, the device conversion efficiency increases to15.94% and 17.05%, respectively.